Costing the conservation of genetic resources: CIMMYT's ex situ maize and wheat collection - Pardey, Philip G.; Koo, Bonwoo; Wright, Brian D.; Van Dusen, M. Eric; Skovmand, Bent; Taba, Suketoshi (Wiley, 2001)
Worldwide, the number of genebanks1 and the amount of seed stored in them has increased substantially over the past few decades. Most attention is focused on the likely benefits of conservation, but conserving germplasm involves costs whose nature and magnitude are largely unknown. Moreover, these costs place a lower bound on the benefits deemed likely to justify the expense of conserving seed. In this study, we compile and use a set of cost data for wheat (Triticum aestivum L.) and maize (Zea mays L.), stored in the CIMMYT genebank to address a number of questions. The marginal costs of holding an existing accession for one more year are presented, along with the costs of conserving saved seed for the life of the genebank (taken here to be 40 yr), and in perpetuity We also investigated the scale economies evident in the CIMMYT genebank operation as a basis for assessing the economics of consolidating several genebanks. For accessions known to satisfy viability requirements, it costs just $0.19 and $0.93 to carry over an existing accession of wheat and maize respectively, for one more year; $7.19 and $30.24 to store an accession of each crop for the life of a genebank, and $10.26 and $58.85 to conserve accessions in perpetuity. Under baseline assumptions about interest rates, capital depreciation, and regeneration regimes, the present value of conserving the existing accessions in perpetuity at CIMMYT is $8.86 million—$3.87 million for storing the 123000 wheat accessions and $4.99 million for the 17000 maize samples. Maintaining the current level of effort to distribute accessions free‐of‐charge to those who request them would cost an additional $5.28 million in perpetuity.